Effects of PVA fibers and nano-SiO2 on rheological properties of geopolymer mortar - Zhang Guo; Zhang Peng; Guo Jinjun; Hu Shaowei (Nanotechnology Reviews)
Geopolymer mortar can be used as an environmentally friendly sustainable construction material for the repair and strengthening of already-existing structures with the utilization of various recycled materials, such as fly ash, slag powder, etc. With mature application of fibers and nanoparticles in construction materials, nano-SiO2 (NS) and polyvinyl alcohol (PVA) fibers have been utilized to enhance the properties of geopolymer mortar, which has a major impact on the rheological properties of geopolymer mortar. The rheological property tests of geopolymer mortar were carried out in this study, and three indices including dynamic yield stress, static yield stress, and plastic viscosity were studied as rheological parameters. The results of the study were used to establish the relationships between PVA fiber content as well as NS content and rheological parameters. The results showed that a tendency of first decreasing and then increasing was observed in the rheological parameters with the addition of NS content from 0 to 2.5%. Compared with the geopolymer mortar without NS addition, the dynamic yield stress, static yield stress, and the plastic viscosity increased by 22.6, 12.4, and 22.9%, respectively, when NS content was 2.5%. The results showed that the rheological parameters of geopolymer mortar increased linearly with the increment in PVA fiber content which was less than 1.2%. In comparison to the geopolymer mortar without PVA fibers, the dynamic yield stress, static yield stress, and plastic viscosity increased by 65, 56, and 161%, respectively, as the PVA fiber content was 1.2%.